Blended finance in the health sector of India - Raju, S. Rajasulochana and Nadar, D. (Economic and Political Weekly)
The blended-financing vehicle created in India during the COVID-19 pandemic provided support to social initiatives in healthcare training and service delivery. The organisation and functioning of blended finance is complex. Thus we put forth some concerns related to its role in the Indian healthcare system.- Reproduced